Unnal mudiyumaa? உன்னால் முடியுமா? - Preuitt, Sheela,Praba Ram,Ashok Rajagopalan (Tulika, 2019)
An intriguing world to discover the different ways in which animals do things that are 'normal'.
Children's story
Keywords: Animals; Juvenile literature.; Animals; Juvenile fiction; Pictorial works.; Children's stories; Tamil.